2020
DOI: 10.12973/ijem.6.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Instructional Design for the Field of ICT and Software for Gifted and Talented Students

Abstract: This study aimed to develop an instructional design that focuses on programming teaching for gifted and talented students and to investigate its effects on the teaching process. During the development of the instructional design; the steps of Morrison, Ross and Kemp Instructional Design Model were followed. Embedded experimental design, one of the mixed-method research designs, was used in the modeling of the study. The participants consisted of students studying at the Science and Art Center (BILSEM) (experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
4
0
1
Order By: Relevance
“…In earlier research performed in SACs, it was discovered that gifted students had high levels of educational technology self-efficacy as well as information and technology literacy skills (Bayra, 2020;Nacaroğlu, 2020). Several educational process experiences that allow gifted students to adapt to new technologies, support their higher-order thinking, and empower them to use and generate with technology may have contributed to their digital literacy abilities (Avcu & Er, 2020a, 2020bAvcu, Ayverdi, Ülker & Karakış, 2020;Ayverdi & Öz;Avcu & Ayverdi, 2022;Avcu & Yaman, 2022;Bozok, Geniş & Avcu, 2020;Çevik, 2021;Del Siegle, 2023;Önal & Önal, 2021). Following the findings of recent research, it can be concluded that gifted students acquired digital literacy, which is a 21st-century skills, through the education they received in SACs (Nacaroğlu, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier research performed in SACs, it was discovered that gifted students had high levels of educational technology self-efficacy as well as information and technology literacy skills (Bayra, 2020;Nacaroğlu, 2020). Several educational process experiences that allow gifted students to adapt to new technologies, support their higher-order thinking, and empower them to use and generate with technology may have contributed to their digital literacy abilities (Avcu & Er, 2020a, 2020bAvcu, Ayverdi, Ülker & Karakış, 2020;Ayverdi & Öz;Avcu & Ayverdi, 2022;Avcu & Yaman, 2022;Bozok, Geniş & Avcu, 2020;Çevik, 2021;Del Siegle, 2023;Önal & Önal, 2021). Following the findings of recent research, it can be concluded that gifted students acquired digital literacy, which is a 21st-century skills, through the education they received in SACs (Nacaroğlu, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…BİLSEM'lerde yürütülmüş olan önceki çalışmalarda, özel yetenekli öğrencilerin teknoloji ve tasarıma yönelik eğitim teknolojileri öz yeterlikleri ve bilgi ve teknoloji okuryazarlığı becerileri yüksek düzeyde bulunmuştur (Bayra, 2020;Nacaroğlu, 2020). Özel yetenekli öğrencilerin yeni teknolojilere uyum sağlamasına olanak tanıyan, üst düzey düşünmelerini destekleyen ve teknolojileri kullanıp teknolojiyle üretim yapmalarını sağlayan birçok öğretimsel süreci deneyimleri özel yetenekli öğrencilerin dijital okuryazarlık becerilerine katkı sağlamış olabilir (Avcu & Er, 2020a, 2020bAvcu, Ayverdi, Ülker & Karakış, 2020;Ayverdi & Öz;Avcu & Ayverdi, 2022;Avcu & Yaman, 2022;Bozok, Geniş & Avcu, 2020;Çevik ve diğerleri, 2021;Del Siegle, 2023;Önal & Önal, 2021). Güncel çalışmaların sonuçları doğrultusunda, özel yetenekli öğrencilerin 21. yüzyıl becerilerinden biri olan dijital okuryazarlık becerisini edinmesinde BİLSEM'lerde özel yetenekli öğrencilere yönelik verilen eğitimle başarıldığı yorumu yapılabilir (Nacaroğlu, 2020).…”
Section: Geniş öZetunclassified
“…Another instructional design developed by Avcu and Er (2020) was effective on the computational thinking and creative thinking skills of gifted students but not on their programming self-efficacy. The instruction also helped the students learn and practise the computational concepts and their applications and develop their perspectives about computational practices, their design thinking skills up to a certain level.…”
Section: Models Of Appropriate Education To Gifted Children Using Ictmentioning
confidence: 96%
“…The instruction also helped the students learn and practise the computational concepts and their applications and develop their perspectives about computational practices, their design thinking skills up to a certain level. The students enjoyed the design thinking process, learned the course content but experienced some difficulties (Avcu & Er, 2020). The authors used the Instructional Design model of Morrison, Ross, Kemp, and Kalman (2010) for this work.…”
Section: Models Of Appropriate Education To Gifted Children Using Ictmentioning
confidence: 99%
“…Positive attitudes, academic achievements, and computational thinking skills with robotic-assisted science education 16 [41] develop an instructional design that focuses on programming teaching for gifted and talented students and to investigate its effects on the teaching process.…”
Section: Snmentioning
confidence: 99%